Impact of phytoecdysteroid treatment on the larval performance of multivoltine mulberry silkworm Bombyx mori Linn. - Pandey, P.; Upadhyay, V.B. (Penerbit Universiti Kebangsaan Malaysia, 2013)
Phytoecdysteroid are being used commercially to shorten the larval duration for synchronize spinning of cocoons and labour saving. In this experiment Achyranthes aspera plant extract containing phytoecdysteroid activity was taken. The experiments were conducted with the phytoecdysteroid concentration of 40, 50, 60 and 70 % and number of treatment viz; single, double,triple. Variation in the number of treatment (P1>0.05) of B. mori larvae significantly influenced the larval duration, larval length, larval weight and survival of larvae. The larval duration decreased from 22.90 days (control) to the minimum of 21.52 days in case of 60%, double treatment of larvae. The larval length increases with the increasing phytoecdysteroid concentration and number of treatment up to 60%, double treatment of larvae. The maximum larval length was recorded to be 6.98 cm in case of 60%, double treatment of larvae while it was minimum (4.90 cm) in 70%, triple treatment of larvae. The weight of larvae increased with the increasing phytoecdysteroid treatment from single to double treatment in 40, 50 and 60% phytoecdysteroid concentration and it was maximum (0.14.36 gm) in 60%, double treatment of larvae. The maximum survival of larvae was noticed to be 95.25±1.55 per cent in case of double treatment of larvae by 60% phytoecdysteroid concentration.